The HPV school vaccination program: A discourse analysis of information provided to parents about the product and the program - Wise, Deborah and James, Melanie Brigid (Public Communication Review, 2012)
Public relations practitioners play a central role in the construction and maintenance of discourse. Through the use of specialised techniques and strategies, texts are designed so that they have the power to mean something. Australia was one of the first countries to roll out a national HPV vaccination program for schoolgirls. However, research indicated that parents lack knowledge about HPV and HPV vaccination. This paper reports on a discourse analysis of the brochure: “Questions and Answers (Q&A) about HPV Vaccination Program: A prevention strategy for cervical cancer”. This brochure is given to parents prior to vaccination and as such is a primary source of information about HPV for these audiences. The research strove to answer the question: What are the discourses contained in the information given to parents about the NSW HPV school vaccination program? A critical discourse analysis of the Q&A brochure found a discourse of the risk of cancer, supported by a discourse that HPV is sexually transmitted. The findings should provide an avenue to further research the role, motivations and techniques of public relations practitioners working as discourse technologists and in whose interests such discourses operate.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTEzMC9wY3IudjJpMS4yMTc5